2000
DOI: 10.1046/j.1467-789x.2000.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Orlistat for the treatment of obesity: rapid review and cost‐effectiveness model

Abstract: The aim of this study is to clarify the potential benefits, disbenefits and costs of Orlistat for the treatment of obesity. The method was a search for relevant systematic reviews and randomized controlled trials, in Medline, Pre-Medline, Embase and the Cochrane Library, using Orlistat and its synonyms. Identified trials were appraised using a standard appraisal checklist and trial data were extracted for use in cost-effectiveness modelling. Three large multicentre, randomized placebo controlled trials were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 17 publications
2
17
1
Order By: Relevance
“…Compared with the basic health state which was anchored to participants' current weight, otherwise identical health states with lower weight (I and J) had significantly higher utilities (increases of 0.02 and 0.03), whereas health states with higher weight (E and F) had significantly lower utilities (decreases of -0.04 and -0.07). This inverse relationship between weight and utility is consistent with findings from previous studies that assessed utilities of patients with type 2 diabetes [9,29,32,33] and obesity [60,[66][67][68]. These previous studies examined the relationship between patients' BMI and utility assessed with questionnaires, most commonly the EQ-5D or Quality of Well-Being Scale.…”
Section: Discussionsupporting
confidence: 87%
“…Compared with the basic health state which was anchored to participants' current weight, otherwise identical health states with lower weight (I and J) had significantly higher utilities (increases of 0.02 and 0.03), whereas health states with higher weight (E and F) had significantly lower utilities (decreases of -0.04 and -0.07). This inverse relationship between weight and utility is consistent with findings from previous studies that assessed utilities of patients with type 2 diabetes [9,29,32,33] and obesity [60,[66][67][68]. These previous studies examined the relationship between patients' BMI and utility assessed with questionnaires, most commonly the EQ-5D or Quality of Well-Being Scale.…”
Section: Discussionsupporting
confidence: 87%
“…The costs per QALY gained for the EMEA criteria were £19,005 compared to £24,431 when NICE criteria were applied. Both of these results were better than a previous estimate of £45,881 per QALY,97 reflecting the more restrictive criteria for the continued use of orlistat, as well as taking into account that prescriptions were almost always provided by general practitioners rather than more expensive hospital specialists. The finding that EMEA criteria resulted in a more favorable estimate indicated that the NICE criteria may have narrowed the treatment population too far 96…”
Section: Economic Considerationscontrasting
confidence: 65%
“…The NNT for 2 years to achieve 5% weight loss using orlistat is 6 (95% CI = 4 to 14), with an estimated treatment cost (at 2007 prices) of £1759 per patient. 30 noting that the present study did not set out to formally measure or compare cost-effectiveness, and these figures are presented mainly to contextualise this study as a lower-cost approach.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%